Pengaruh Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Keberhasilan UMKM di Kecamatan Bulakamba - Ismi Chasani; Dumadi; Roni (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to determine and analyze the influence of accounting information systems and internal control on the success of MSMEs. The data used are primary data obtained from distributing questionnaires to several MSMEs in Bulakamba District. The sample in this study was 95 respondents. The sample determination method is Purposive Sampling. The analysis used is multiple linear regression analysis using the SPSS 25 program. The results of the study stated that the accounting information system has a partial effect on the success of MSMEs with a contribution of 26.3%, internal control has a partial effect on the success of MSMEs with a contribution of 21.8%, accounting information systems and internal control have a simultaneous effect on the success of MSMEs with a contribution of 21.8%. The success of MSMEs can be explained by the variation of two independent variables of 40.9%. There needs to be more attention from the local government so that MSMEs can grow further.